Agrobiological and economic potential of wine grapevine cultivars grown in the Kyustendil region, Bulgaria - Krumov Simeon D.; Krishkova Iliyana S.; Simeonov Iliyan N. (Journal of Agricultural Sciences (Belgrade))
A comparative analysis of the agrobiological and economic potential of 2 white ('Slava' and 'Droujba') and 3 red ('Kaylashki rubin', 'Trapezitsa' and 'Rubin') wine grapevine cultivars under the soil and climatic conditions of the Kyustendil region in Bulgaria was carried out. Comparative variants (standards) for red cultivars were 'Pamid', and for white cultivars - 'Tamyanka'. The study was conducted during the period 2021-2024 in a collection vineyard of the Institute of Agriculture - Kyustendil, Bulgaria. In terms of quality, fertility and size of the bunches and berries, the studied cultivars reached and even exceeded the values characteristic for each of them. The percentage of berries in the bunch was "high" in all variants - from 95.0% for 'Trapezitsa' to 97.2% for 'Kaylashki rubin' and 'Droujba'. The grapes of the 'Pamid' and 'Tamyanka' standards, as well as the interspecific cultivars 'Droujba' and 'Kaylashki rubin', were characterized by a "very high" theoretical yield. In economic terms, the best results, under the experimental conditions, were achieved with the red cultivars 'Trapezitsa' and 'Kaylashki rubin'. The high level of net income and profitability show that the white cultivar 'Droujba' also has considerable economic potential.